Efficacy of chemotherapy combined with toripalimab in PD-L1–positive and high tumor mutation burden pancreatic acinar cell carcinoma: case report. Issue 6 (December 2021) - Xu, Huanji; Wang, Xin; Zhou, Sheng; Hu, Qiancheng; Cao, Dan
Background: Pancreatic acinar cell carcinoma (PACC) is a rare tumor, accounting for about 1% of all pancreatic exocrine cancers. Consensus on the management of metastatic PACC remains unclear. Case presentation: Starting from April 2019, a patient first received chemotherapy with two cycles of gemcitabine and nab-paclitaxel and two cycles of SOX regimen. After progression of disease evaluated based on RECIST 1.1, toripalimab and SOX regimen was administered because of PD-L1–positive expression, high tumor mutation burden (TMB), and somatic FANCA deletion in the tumor. Both the primary and metastatic tumor mass shrank significantly after two courses. The patient exhibited sustained partial response for at least six courses with well-controlled toxic effects. Then the treatment had to be stopped for 2 months because of the coronavirus disease 2019 pandemic. Computed tomography scan in March 2020 showed disease progression. Time from initiating treatment to tumor progression on toripalimab and SOX regimen treatment took up to at least 8 months. Conclusions: We present the first case report where a PD-L1 positive, high TMB, and FANCA -deleted pancreatic acinar cell carcinoma was treated using chemotherapy combined with immunotherapy, in which the patient exhibited satisfactory response and tolerance.